2011
DOI: 10.1530/jme-11-0002
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor α and retinoids are key regulators in apoptosis of trophoblasts of patients with recurrent miscarriages

Abstract: The retinoid X receptor a (RXRa) is a nuclear hormone receptor that is able to bind other nuclear receptors in a heterodimeric complex, thereby activating gene transcription. Recently, we identified enhanced expression of RXRa in extravillous trophoblasts (EVT) and villous trophoblasts (VT) of miscarried placentas. In addition, an increased number of apoptotic EVT was present in miscarried placentas. In this study, on the basis of immunocytochemical analysis, western blots, and quantitative real-time reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Already decades ago, the natural binding partner of PPAR, the RXR was described in this trophoblast compartment: RAR and RXR, both types of receptors were present in the proliferative intermediate villous trophoblast [33]. Later, RXR was found to play a crucial role in pregnancy and is a key regulator of apoptosis in trophoblasts of patients with recurrent miscarriages [9]. PPAR on the other hand was also described to be dysregulated in different trophoblast compartments of the miscarriage placenta [34,35], although PPAR expression in the IVT was never investigated before.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Already decades ago, the natural binding partner of PPAR, the RXR was described in this trophoblast compartment: RAR and RXR, both types of receptors were present in the proliferative intermediate villous trophoblast [33]. Later, RXR was found to play a crucial role in pregnancy and is a key regulator of apoptosis in trophoblasts of patients with recurrent miscarriages [9]. PPAR on the other hand was also described to be dysregulated in different trophoblast compartments of the miscarriage placenta [34,35], although PPAR expression in the IVT was never investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR together with its heterodimer binding partner retinoid X receptor  (RXR) are involved in cell proliferation, cell differentiation, and organogenesis [8]. RXR is upregulated in extravillous trophoblast in recurrent miscarriages in humans [9]. RXR plays a pivotal role in the receptor family, due to its ability to form heterodimers with other nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear retinoid X receptor (RXR), which is involved in cell proliferation, cell differentiation, and organogenesis, 2 is upregulated in extravillous trophoblast in recurrent miscarriages in humans. 3 RXR plays a pivotal role in the receptor family, due to its ability to form heterodimers with other nuclear receptors. Heterodimer partners are e.g.…”
Section: Introductionmentioning
confidence: 99%
“…4-6 Especially the expression of the isoform PPARγ is linked to trophoblast invasion 7-9 and downregulation of the isoform RXRα seems to protect against apoptosis in human trophoblasts. 3 LXR is a physiological regulator of lipid and cholesterol metabolism and inflammation, 10 of trophoblast invasion and maternal-fetal cholesterol transport. 11,12 These nuclear receptors are crucially involved in maintaining a viable pregnancy, their role had been clarified especially in human trophoblastic tissue: Toth et al showed that extravillous trophoblast (EVT) in placentas of miscarriages show a significantly higher expression of RXRα in comparison to EVT in placentas of elective termination of healthy pregnancies.…”
Section: Introductionmentioning
confidence: 99%